Viscosity dictates metabolic activity of Vibrio ruber - Boric, Maja; Danevcic, Tjasa; Stopar, David (Frontiers in Microbiology, 2012)
Little is known about metabolic activity of bacteria, when viscosity of their environment changes. In this work, bacterial metabolic activity in media with viscosity ranging from 0.8 to 29.4 mPas was studied. Viscosities up to 2.4 mPas did not affect metabolic activity of Vibrio ruber. On the other hand, at 29.4 mPas respiration rate and total dehydrogenase activity increased 8 and 4-fold, respectively. The activity of glucose-6-phosphate dehydrogenase increased up to 13-fold at higher viscosities. However, intensified metabolic activity did not result in faster growth rate. Increased viscosity delayed the onset as well as the duration of biosynthesis of prodigiosin. As an adaptation to viscous environment V. ruber increased metabolic flux through the pentose phosphate pathway and reduced synthesis of a secondary metabolite. In addition, V. ruber was able to modify the viscosity of its environment.